A Synchronous Occurrence of Urothelial Carcinoma with Abundant Myxoid Stroma and Inverted Papilloma of the Urinary Bladder - Kemal Behzatoğlu; Pelin Yildiz; Meltem Öznur; Erol R. Bozkurt (Rare Tumors, 2012)
Abundant myxoid stroma rarely occurs in urothelial carcinomas, and may cause diagnostic challenges when cells with eosinophilic cytoplasm forming nests and cords in a myxoid background are seen, particularly in the absence of typical carcinomatous appearance. Microscopic examination of transurethral resection specimen of a 71-year-old male patient revealed non-cohesive oval or elongated tumor cells with eosinophilic cytoplasm arranged in cord-like filigree pattern in an abundant myxoid stroma. Immunohistochemically the tumor was positive for cytokeratin 7, cytokeratin 20, and 34BE12. About 90 to 100% nuclear staining was observed with p63, p53, and Ki-67. A second neoplasm with a flat overlying urothelial epithelium and a complete inverted cellular growth pattern was also noted. The neoplasm exhibited less than 2% and 10% nuclear staining with Ki-67 and p53, respectively. Considering histological, histochemical, and immunohistochemical findings, a diagnosis of synchronous urothelial carcinoma with abundant myxoid stroma and inverted papilloma was made.